Menyoal Konsep Kesembuhan Tubuh: Suatu Kajian Teologis: Questioning the Concept of Body Healing: A Theological Study - Kalis Stevanus (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
The Bible records many texts dealing with the subject of healing the body. This study uses a literature approach by digging sources from journal articles and books and then analyzing them using the Bible to produce in-depth and comprehensive theological conclusions. The conclusion of this study shows that healing of the body can occur through natural healing, medical healing, and divine healing miracles or miracles. The implication is theological; Christians may believe that miracle healing still exists and can pray to God so that healing that comes from Him can be experienced now. And the practical implication is that Christians must still be responsible for taking care of their bodies' health proportionally because their bodies are the temple of God.